The Beneficial Effects of Curcumin on Lipids: Possible Effects on Dyslipidemia-induced Cardiovascular Complications - Yaribeygi, Habib; Maleki, Mina; Butler, Alexandra E.; Jamialahmadi, Tannaz; Gumpricht, Eric; Sahebkar, Amirhossein (Current Medicinal Chemistry, 2024)
Dyslipidemia and altered lipid metabolism are closely involved in the pathogenesis and clinical manifestation of many metabolic and non-metabolic diseases. Therefore, mitigation of pharmacological and nutritional factors together with lifestyle modifications is paramount. One potential nutraceutical exhibiting cell signaling and lipid-modulating properties implicated in dyslipidemias is curcumin. Specifically, recent evidence suggest that curcumin may improve lipid metabolism and prevent dyslipidemia-induced cardiovascular complications via several pathways. Although the exact molecular mechanisms involved are not well understood, the evidence presented in this review suggests that curcumin can provide significant lipid benefits via modulation of adipogenesis and lipolysis, and prevention or reduction of lipid peroxidation and lipotoxicity via different molecular pathways. Curcumin can also improve the lipid profile and reduce dyslipidemia-dependent cardiovascular problems by impacting important mechanisms of fatty acid oxidation, lipid absorption, and cholesterol metabolism. Although only limited direct supporting evidence is available, in this review we assess the available knowledge regarding the possible nutraceutical effects of curcumin on lipid homeostasis and its possible impacts on dyslipidemic cardiovascular events from a mechanistic viewpoint.
Keywords: curcumin